APLIKASI PEMBERIAN PROBIOTIK YANG BERBEDA IKAN LELE SANGKURIANG (Clarias gariepinus) DI DESA BANYUAJUH KAMAL BANGKALAN - Erika Noviyana Efendy; Ridha Olnis Syawallita; Muhammad Zainuri; Abdus Salam Junaedi (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2023)
Aquaculture activities play an important role in fulfilling aquaculture commodities. One of them is catfish farming activities. Complex problems related to feed efficiency in the fisheries sector are related to the ever-increasing price of feed. Adding fish probiotics to feed is an alternative solution for cultivation businesses. The aim of this research is to determine the comparative effect of different probiotic applications on physical, chemical and biological factors in water, weight and length increase in catfish (Clarias gariepinus). This research is an experimental study using 3 types of probiotic treatments (MinaPro, YEB Consortium, and control). The pond used in this research measures 2x2 m2 and contains 240 individuals. The results of temperature measurements in all treatments were 27.64-32.18 ̊C. The pH measurement results were 5.118-14.15. Results of salinity measurements with a value of 0 ppt. The results of measuring the dissolved oxygen value were 0.345-8.908 ppm. The use of different types of probiotics had an effect on the growth of catfish (Clarias gariepinus) with the best treatment using the MinaPro probiotic with an average final weight of 15.59 kg with a length of 14.54.